Minimal Structural Changes Determine Full and Partial Nicotinic Receptor Agonist Activity for Nicotine Analogues - Reyes-Parada, M (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
Neuronal α4β2 nicotinic acetylcholine receptors (nAChRs) are ligand-gated ion channels (LGIC) that have been implicated in nicotine addiction, reward, cognition, pain disorders, anxiety, and depression. Nicotine has been widely used as a template for the synthesis of ligands that prefer α4β2 nAChRs subtypes. The most important therapeutic use for α4β2 nAChRs is as replacement therapy for smoking cessation and withdrawal and the most successful therapeutic ligands are partial agonists. In this case, we use the N-methylpyrrolidine moiety of nicotine to design and synthesize new α4β2 nicotinic derivatives, coupling the pyrrolidine moiety to an aromatic group by introducing an ether-bonded functionality. Meta-substituted phenolic derivatives were used for these goals. Radioligand binding assays were performed on clonal cell lines of hα4β2 nAChR and two electrode voltage-clamp experiments were used for functional assays. Molecular docking was performed in the open state of the nAChR in order to rationalize the agonist activity shown by our compounds. © 2019 by the authors.